2005
DOI: 10.2320/matertrans.46.2484
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Diffusion Bonds between TiAl Intermetallic Compound and Titanium Alloy

Abstract: To investigate the feasibility of joining the TiAl intermetallic compound to titanium alloys, the diffusion bonding of TiAl to Ti-17 alloys (Ti-Al-Cr-Mo-Sn-Zr, near -phase alloy) was performed, and the effects of joining parameters on the joint strength and the diffusion phase at the bonding interface were examined.The major results are as follows:(1) For diffusion bonding of TiAl to Ti-17, joints which fractured at the TiAl base metal on the tensile test were obtained in case where the thickness of the diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…This indicates that part of TiAl based alloy was tore during the fracture process, namely the strength of local region of the joint has exceeded the strength of the TiAl based alloy matrix. This result is similar to the performance of the diffusion bonded joint between TiAl based alloy and Ti–Al–Cr–Mo–Sn–Zr alloy .…”
Section: Resultssupporting
confidence: 82%
“…This indicates that part of TiAl based alloy was tore during the fracture process, namely the strength of local region of the joint has exceeded the strength of the TiAl based alloy matrix. This result is similar to the performance of the diffusion bonded joint between TiAl based alloy and Ti–Al–Cr–Mo–Sn–Zr alloy .…”
Section: Resultssupporting
confidence: 82%
“…Wang et al [ 69 ] reported that the interfacial phase sequence of the diffusion bonded joint was identified as Ti-43Al-9V/γ-TiAl/B 2 /α 2 -Ti 3 Al/α-Ti/Ti-6Al-4V, as shown in Figure 9 [ 69 ]. Kanai et al [ 87 ] also confirmed the formation of Ti 3 Al phase when diffusion bonding TiAl to Ti-17 alloys. Holmquist et al [ 85 ] analyzed the tensile and creep properties of diffusion bonded IMI 384 titanium alloy to IHI 01A γ-TiAl joint.…”
Section: Diffusion Bonding Of Titanium Aluminidesmentioning
confidence: 90%
“…The diffusion bonding between titanium aluminides and Ti alloys was systematically investigated in the existing literature [ 67 , 69 , 85 , 87 , 88 ]. According to elemental gradient diffusion at the interface, the preferred reaction phase betwen TiAl intermetallics to TC4 alloys is α 2 -Ti 3 Al phase.…”
Section: Diffusion Bonding Of Titanium Aluminidesmentioning
confidence: 99%
“…Furthermore, residual stress analysis due to the difference in the coefficient of thermal expansion was reported for the cases where silicon carbide and alumina were welded with the aid of up to several interlayers or FGM. 7 A study of direct joining of metal and ceramic using ultrasonic waves for energy supply was reported. 8 Joining to the degree that strength evaluation was just viable was obtained between metals with a relatively low melting point and ceramics with a small surface roughness.…”
Section: Welding and Joining Of Ceramicsmentioning
confidence: 99%
“…Laser welding of forged TiAl intermetallic compound alloys indicated a low strength for as-welded conditions but a strength equivalent to that of the base metal was achieved by post-weld heat treatment at 1374 K. 6 In addition, the joining of TiAl and dissimilar metal was also carried out; when joining with Ti-Al-Cr-Mo-Sn-Zr alloy, joints which fractured in the TiAl were obtained. 7 Joining trials of TiAl and TiC cermets were also undertaken by means of combustion synthesis using a Ti-Al-C-Ni interlayer. 8 Reviews of the reactive joining of aluminide-based intermetallic compounds were summarised.…”
Section: Welding and Joining Of Advanced Metallic Materialsmentioning
confidence: 99%